The Influence of Environmental, Social, Governance and Capital Structure Performance on Financial Performance - Fajar, Kemaludin Rahmat; Effriyanti, Effriyanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This study aims to analyze the influence of Enviromental, Social and Governance (ESG), and capital structure on financial performace. This type of research is quantitative research with secondary data sources. The population in this study is financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sample selection method used in this study is purposive sampling wich undergoes an outlier process, so that the final sample obtained is 10 companies. The result of the study shows that silmutaneously the variables of Enviromental, Social and Governance (ESG) and capital structure have an effect on financial performance. The result show that companies had high ESG scores and low capital structures can improve their financial performance. Then partially the Enviromental, Social and Governance (ESG) variables have an influence on financial performance. The result show that companies with high ESG scores have the potential to improve the company’s financial performance. Furthermore, the capital structure variable has no effect on financial performance. The result show that Bank companies with a large amount of debt cannot affect the company’s financial performance.